Dynamising Liberation Movements in Southern Africa - Chidochashe Nyere (African Journal of Political Science)
The book grapples with reconciling the ideological, policy and implementation bankruptcy of former liberation movements in Southern Africa especially as it applies to their incumbency of national government in their respective domains. The main thesis of the book is that prior to ascending to national government, these liberation movements seemed to have the relevant ideological muscle that reflected the axiology of their times, especially South Africa’s African National Congress (ANC) and the Zimbabwe African National Union (ZANU). Conversely, these liberation movements plainly failed to translate the same axiological arsenal to relevant policy, implementation and practice once they morphed into national government. It is this dissimulation that raises questions on their seeming un-fit for purpose. Undoubtedly, prior to incumbency these movements identified with the masses; they represented the future and a trajectory that embraced the aspirations of many. Sadly, those aspirations remain just but figments of imagination for many people that supported these movements now that these liberation movements have formed governments. Without recalibrating their objectives, visions, and aspirations these liberation movements risk being relegated to political dustbins as they have proverbially reached an ideological cul-de-sac.